Financial Literacy Assistance in Banking Products (BPRS Mitra Harmoni) to Primary School Students in Increasing Financial Awareness from an Early Time (Study at Madrasah Ibtidaiyah Malang) - Nazylah, Choirun; Umamah Listya R, Sayidah; Rinawati, Ika (Sahwahita: Community Engagement Journal, 2024)
The importance of managing finances from an early age aims to ensure that people can manage their finances personally and become financially free. Financial institutions or schools need to take important steps to participate in providing literacy to students from the elementary school level up. The activity method consists of the Activity Planning stage, implementation stage, and closing or observation stage. The results of the literacy activities are: first, providing PowerPoint material. The material contains material that explains various financial institutions and their benefits for our lives in the future. Second, watch a video together, an animated video that contains how to carry out financial transactions at financial institutions correctly, the benefits and goodness that can be obtained when someone diligently saves and puts their money in an official financial institution, the convenience of saving facilities without having to come to a BPRS financial institution Harmony Partners. Third, distribution of financial institution literacy media in the form of brochures and registration forms. Fourth, practice saving. Students practice saving by filling in the account opening registration form as the first step that must be taken. Then the students deposit money as an initial deposit of IDR 10,000.00 to the officer in the cash car. Closing Activities or Evaluation from MI Wahid Hasyim School there are 103 customers and MI NU Sumberpasir School there are 123 customers.